Efgartigimod following plasma exchange in the treatment of subjects with generalised myasthenia gravis: study protocol for a multicentre, three-arm, open-label study - Lu Zhang; Kan Wang; Yong Hao; Yangtai Guan; Jing Peng; Li Gao; Song Gao; Qiuju Li; Chong Xie; Yuhui Wang; Yanan Wu; Mengze Zhang; et al. (BMJ Neurology Open)
Introduction Myasthenia gravis (MG), an IgG-mediated autoimmune disorder targeting neuromuscular junctions, shows refractory in 12–20% of generalised MG (gMG) patients despite immunotherapies. Plasma exchange (PLEX) transiently depletes pathogenic mediators, while neonatal Fc receptor antagonists (eg, efgartigimod) offer novel therapeutic potential. Both PLEX and efgartigimod require adjunctive non-steroidal immunosuppressive therapy (NSIST) for sustained remission. This study aims to evaluate the effectiveness and safety of efgartigimod working as a bridge treatment after PLEX but before NSIST taking effect, while concurrently conducting a comparative analysis of clinical outcomes between PLEX and efgartigimod in gMG.Methods and analysis This multicentre, open-label, three-arm trial (n=45 gMG patients) assigns cohorts to PLEX+efgartigimod, PLEX alone or efgartigimod alone. The intervention comprises PLEX and/or efgartigimod. Oral glucocorticoids and cholinesterase inhibitors are allowed during this study. NSIST starts the day after completing PLEX or the second dose of efgartigimod. Outcomes are assessed at weeks 4, 8, 12, 16, 20, 24, 36 and 48. Primary endpoint: proportion achieving minimal symptom expression (MSE) at week 48. Secondary endpoints: median time to first MSE, adverse events (AE) incidence/severity, exacerbation rates, neurological functional assessment scores, cholinesterase inhibitor/corticosteroid usage, serological evolution of immunological markers. All AEs are systematically documented and causality-assessed.Ethics and dissemination Ethical clearance for this investigation was granted by the Institutional Review Board of Punan Hospital in accordance with Declaration of Helsinki principles. All enrolled participants will provide written informed consent through standardised documentation processes prior to study enrolment. The results will be accessible in peer-reviewed publications.Trial registration number ChiCTR2500104662.